The Influence of Work-Life Balance and Job Stress on Turnover Intention through Job Satisfaction among Employees of PT Adira Dinamika Multi Finance Sidoarjo - Fitri Astutik; Lucy Larassaty (Universitas Nahdlatul Ulama Sidoarjo, 2026)
This study aims to analyze the effect of work-life balance and job stress on turnover intention mediated by job satisfaction among employees of PT Adira Dinamika Multi Finance Sidoarjo. Data were collected through questionnaires distributed to 61 respondents who were employees in the sales and marketing divisions of PT Adira Dinamika Multi Finance Sidoarjo. This study employed a quantitative research method with an explanatory research approach. The analytical method used was Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS 4.0 software.The results of the study indicate that job stress has a positive and significant effect on turnover intention, while work-life balance has a positive and significant effect on job satisfaction. However, work-life balance does not have a significant direct effect on reducing turnover intention. The findings also reveal that job satisfaction does not have a significant effect on turnover intention and is unable to mediate the effect of work-life balance and job stress on turnover intention.